The Quaternary vertebrate fauna of cave deposits of the Podillia-Bukovynian Karst-Speleological Area (Western Ukraine) - Ridush, Bogdan (Stratigraphy & Timescales. V.7, 2022, Academic Press, Elsevier, 2022)
The Podillia-Bukovinian Karst-Speleological Area is rich in numerous caves of karst, suffosion, and weathering origin. The gypsum karst is the most widespread in the area. It is famous for the World’s largest maze-caves in gypsum. Some of these caves contain Quaternary sediments with vertebrate fauna that can be used for biostratigraphy. The first faunal remains were found as early as 1886. Up to now, at least 30 cave sites with Quaternary vertebrate fauna are known. Most of the sites are in horizontal caves, which results in specific bone- and sediment accumulations. The formation of most of the bone accumulations is related to the inhabitation of caves by the troglophilic species, especially carnivores, and only a few inhabited by humans. The oldest among the cave sites is Chortkiv, dated to the late Odesian Fauna (Kryzhanivka Stage, MIS 41-62). The best-studied cave sections with cave fauna are Bukovynka, Kryshtaleva (Kryvchanska), Pryima I, Chortovi Skeli (Lviv VIII). Several caves are promising for further research, such as Martynivka, Tovtry, and others. A very small part of the osteological material was published in detail. Only 15 radiocarbon dates are known for the cave sites in the region. Many finds in the caves were made in the 1950s-1960s, sometimes just by accident. Part of the bone collections were lost. The material stored in museums should be revised. There still is a large potential for the future research of the Quaternary cave deposits of the Podillia-Bukovynian Karst-Speleological Area (Western Ukraine).
Keywords: Quaternary; cave deposits; karst; Podillia-Bukovynian Karst-Speleological Area; mammalian fauna